ANALISIS DEFORMASI GUNUNG AGUNG SAAT ERUPSI DESEMBER 2018 - JANUARI 2019 BERDASARKAN DATA PENGAMATAN GPS - Abdillah P, Adam
Before returning to active in 2017, the last Mount Agung eruption occurred in 1963 where 1,148 people were killed. Since August 10, 2017 until now, Gunung Agung is at level III (Standby) and several times are at level IV (Beware) with dozens of eruptions occurring. The purpose of this study was to observe the deformation activity of Mount Agung when pre and post eruption using the GPS observation method. The Gunung Agung deformation activity took the form of a type of deformation and deflationary inflation activity that occurred in the body of Mount Agung when it was pre and post-eruption. The study began with the installation of 4 observation GPS stations at the Gunung Agung perimeter since December 11, 2018 and data was collected on January 24, 2019. Analysis of the type of deformation on the body of Mount Agung is based on changes in the value of coordinates that occur at the four observation points in the horizontal direction. While the analysis of inflation and deflation activities on the body of Gunung Agung is based on changes in the value of the four observation points and changes in the baseline length of the four observation points. The inflation deformation activity on the body of Mount Agung always occurs during pre-eruption and deflation occurs when posteruption. The change in baseline observations shows that inflation and deflation activity are predominantly by the moving of observation points at East and West. Based on the results of data processing, it can be seen that eruptions 19, 21, and January 22, 2019 are one eruption series. With the existence of this study, the pattern of the deformation activity of thebody of Gunung Agung is expected to be used for the purposes of erupting mountain potential studies that will occur in the future.